Analisa Sistem Perawatan Lift Gedung Moch Ihsan Balai Kota Semarang - Rahmadhani, Refinda; Yahya, Pulung Septian; Hartono, Nugroho; Supriyo, Supriyo (Politeknik Negeri Semarang, 2014)
The elevator is a vertical transport equipment that is used as a tool to facilitate the activities both human and goods to lead up particular floor in buildings. Moch. Ichsan building is one-storey building in Semarang that use elevator as transportation vertical lift. It needs effective and efficient elevator planning in order to operate the lift optimally. This should be very influential the building occupants comfort as lift users. One of the consequences of lack maturation of the lift planning is the queque during rush hours. As a result it is required some analysis of the existing elevator in Moch.Ichsan building. Elevator efficiency can be analyzed by calculated elevator needs that has a dependency on several variables such as speed lift, lift capacity, lift waiting time, number of buildings' residents, and how large the building is. While lift effectiveness could be obtained from schedulling preparation and budget needs involved in any preventive maintenance lift. Research methodology used in this study are interview, observation, secondary data collection, and data processing. From the results of data processing can be concluded that the efficiency and effectiveness of the elevator by 75% lift need are 4 units while the lift provided only 3 unit. The result also showed some schedule preventive maintenance and preventive maintenanceon lift budget in one year period.